Bacteriorhodopsin monolayers for medical applications: self-assembly and characterization - Oliveira, Mafalda Gonçalves (2021)
Manipulating bacteriorhodopsin (bR) into a monolayer form has become of growing interest for inclusion in nanodevices for medical purposes such as artificial retina development, mammogram processing optimization and neural silencing. The efficient photoconverting protein’s thermal and chemical stabilities are such that bR has become an attractive candidate for protein-based nanostructures, as opposed to other biomolecules. In this type of molecular-scale manipulation, assembling monolayers with high degree of orientation and protein functionality preservation are of paramount importance. The present work focuses on covalent attachment of 247Cys bR mutant monolayers to a strategically engineered gold substrate through self-assembly process. Covalent attachment of bR in its native form, or purple membrane (PM), on engineered mica substrate is also achieved. Liquid sample characterization via absorption, circular dichroism and steady-state fluorescence spectroscopies is performed as well as absorption spectroscopy on bR deposited on gold substrate and AFM topographic studies on both substrates.